Comparative Analysis of Gasoline and Biofuel Impacts on the Performance, Emissions, and Wear of Motorcycle Engines Over Long-term Operating Conditions - Nghia, Nguyen Tuan; Khoa, Nguyen Xuan (Engineering, Technology & Applied Science Research, 2025)
In this study, experimental methods were employed to evaluate the impact of E10 fuel, a renewable fuel source, on the engine performance and wear of key engine components, such as pistons, cylinders, and piston rings. Two 100cc motorbike engines, running on RON 92 and E10 gasoline, were tested over a cycle equivalent to 20,000 km. The results indicated that for RON 92 engines, the average power loss was 5.48%, while for E10 engines, it was 6.08%. Fuel consumption increased, with RON 92 vehicles showing an average rise of 6.55%, compared to 7.27% for E10 biofuel motorbikes. In terms of emissions, vehicles running on RON 92 experienced a 3.83% increase in HC, a 4.17% in NOx, a 3.7% increase in CO2, and a 3.17% rise in CO. For motorbikes using E10 biofuel, HC increased by 3.85%, NOx by 4%, CO2 by 5.16%, and CO by 4.02%. The wear of critical engine components was 0.02% higher when using E10 compared to RON 92. Future research should focus on investigating different ethanol concentrations, fuel-injection engine types, or hybrid drive systems.